Pengaruh Content marketing Dan Influencer marketing Terhadap Keputusan Pembelian Produk Scarlett Pada Mahasiswa Fakultas Ekonomi dan Binis Universitas Trunojoyo Madura - Fina Ayu Alvionita; A. Yahya Surya Winata (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
The purpose of this research is to find the impact of content and influencer marketing to purchase decisions of scarlett product among the students of Faculty Economic Bussnies, Universitas Trunojoyo Madura. The research sample consisted of 110 respondents who had seen the content and had used Scarlett products. Data was collected through an online questionnaire and the research method used was multiple linear regression analysis with SPSS.Result of this research shows that content marketing has a positive and significant impact on purchasing decisions for Scarlett products, while influencer marketing also has a positive and impact influence on purchasing decisions for Scarlett products. These results indicate that a marketing strategy combining relevant content and popular influencers can increase purchasing decisions for Scarlett products among FEB students at Universitas Trunojoyo Madura.